Analisis Efektivitas Promosi Digital Event Kemah Budaya dalam Meningkatkan Brand Awareness Desa Wisata Cikalahang - Dian Fitriyana; Yuke Hernawati (International Forum of Researchers and Lecturers, 2026)
Tourism is a vital sector in economic and social development; however, many regions face challenges in optimizing their tourism potential, especially in the digital era. Cikalahang Village in Cirebon Regency has several tourist attractions that have not been optimally marketed. Therefore, innovative strategies are needed to develop sustainable tourism by utilizing digital technology. This study aims to analyze the effectiveness of digital promotion of events in increasing the brand awareness of Cikalahang Tourism Village. The development of information technology encourages tourism destination managers to utilize digital media as an effective promotional tool, particularly in introducing tourism events to a wider audience. The Cultural Camp Event is one of the promotional strategies used to attract tourists and strengthen the image of the tourism village. The urgency of this research arises from several challenges, such as limited human resources, lack of training, and low utilization of digital media as a promotional tool for cultural events. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. Informants in this study include tourism village managers and Pokdarwis (tourism awareness groups). Data analysis was carried out through data reduction, data presentation, and conclusion drawing. Nevertheless, there is significant potential for further development through social media-based marketing strategies, improving product quality, and strengthening local branding.